Interobserver Variability of Target Volumes Delineated in the Supine and Prone Positions Based on Computed Tomography Images for External-Beam Partial Breast Irradiation After Breast-Conserving Surgery: A Comparative Study - Yu, Ting; Li, YanKang; Wang, Wei; Li, Fengxiang; Wang, Jinzhi; Xu, Min; Zhang, Yingjie; Li, Jianbin; Yu, Jinming (Frontiers in Oncology, 2020)
Background: Although the supine position remains the dominant position for external-beam partial breast irradiation (EB-PBI), the advantages of administering EB-PBI in the prone position have been recognized. The interobserver variability between target volumes delineated in the different positions for EB-PBI after breast-conserving surgery needs to be investigated. Methods: Twenty-seven patients suitable for EB-PBI were enrolled from July 2016 to April 2017. Supine and prone simulation CT images were sequentially acquired for all enrolled patients during free breathing. Five experienced radiotherapists delineated the target volumes for all patients on supine and prone simulation CT images. The selected parameters, including the target volumes, coefficient of variation (COV), matching degree (MD) and so on, were calculated to analyze interobserver variability. Results: Regardless of patient position, the interobserver variability between tumor bed (TB) and clinical target volume (CTV) measurements in supine and prone positions were statistically significant (F=31.34, 19.467; 44.000, 41.985; P=0.000, 0.001; 0.000, 0.001). The interobserver variability of COVCTV was significantly greater in the supine position than in the prone position (T=2.64, P=0.014). Furthermore, the interobserver variability of MDTB and MDCTV were statistically lower in the supine position than in the prone position (Z=-3.460, -3.195, P=0.000, 0.001). Conclusion: When delineating the target volume for EB-PBI, the interobserver variability in the prone position was lower than that in the supine position. Hence, the administration of EB-PBI in the prone position during free breathing is a reasonable option.